Efficient Route Discovery and Link Failure Detection Mechanisms for Source Routing Protocol in Mobile Ad-Hoc Networks - Khudayer, Baidaa Hamza; Anbar, Mohammed; Hanshi, Sabri M.; Wan, Tat-Chee (IEEE access, 2020)
The rapid advances in the wireless communication industry have paved the way for the enhancement of wireless mobile ad-hoc networks (MANETs) to support various domains including civilian environments, emergency operations, and military affairs. Source routing in MANETs is subject to some issues such as changes in the network topology, which lead to frequent link breakages that may increase the requests of route discoveries. Thus, this paper aims to enhance on-demand source routing protocols by proposing two mechanisms, a zone-based route discovery mechanism (ZRDM) and a link failure prediction mechanism (LFPM). ZRDM aims to control the flooding of route requests, and LFPM aims to avoid route breakages caused by node mobility. The performance of the proposed mechanisms was evaluated using network simulator 3 in terms of normalized routing load, average end-to-end delay, and packet delivery ratio. The experimental results showed that the proposed mechanisms outperform well-known mechanisms such as the dynamic source routing (DSR) protocol, reliable DSR, and zone-based DSR and segment-based DSR.